The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1161/circulationaha.110.964171
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Renal Outcomes With Telmisartan, Ramipril, or Both in People at High Renal Risk

Abstract: dual therapy did not reduce cardiovascular or renal outcomes compared with either angiotensin-converting enzyme inhibitors or angiotensin receptor blockers alone. Previous controlled trials with angiotensin-converting enzyme inhibitors or angiotensin receptor blockers have demonstrated greater cardiovascular and renal benefit in people with renal risk. We hypothesized that dual therapy would be more effective than monotherapy in patients with low glomerular filtration rate and elevated albuminuria. Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(68 citation statements)
references
References 37 publications
3
62
0
3
Order By: Relevance
“…Long-term studies are required to test whether prevention of aldosterone breakthrough by cautious dual ACEI/ARB blockade in specific patient populations (29,30) or aldosterone inhibitors (31) would lead to improved nephroprotection. …”
Section: Discussionmentioning
confidence: 99%
“…Long-term studies are required to test whether prevention of aldosterone breakthrough by cautious dual ACEI/ARB blockade in specific patient populations (29,30) or aldosterone inhibitors (31) would lead to improved nephroprotection. …”
Section: Discussionmentioning
confidence: 99%
“…19 Surprisingly, the authors did not find any protective effects of dual therapy on hard renal and cardiovascular outcomes. Important within this context is the question of what dual therapy did to blood pressure and albuminuria.…”
Section: Article See P 1098mentioning
confidence: 94%
“…18 In the current issue of Circulation, Tobe et al report on the TRANSCEND (Telmisartan Randomized Assessment Study in ACE Intolerant Subjects with Cardiovascular Disease) trial, in which the ARB telmisartan is compared to placebo in patients intolerant to ACEi. 19 They demonstrate greater treatment effects on renal outcomes in patients with GFR below 60 mL/min and micro-or macroalbuminuria. Interestingly, in patients with normoalbuminuria, telmisartan had no beneficial effect, and it increased the risk of renal events compared with placebo.…”
Section: Article See P 1098mentioning
confidence: 99%
“…Moreover, the risk of cardiovascular comorbidities has not differed significantly between treatment and placebo (LE Ia, Ib). [22][23][24][25][26] It has been shown that 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors (statins) significantly reduce the risk of death, stroke or coronary disease in hyperlipidemic patients with impaired GFR, but no large trials have reported outcome data for albuminuric subjects. [27][28][29][30] b blockers reduce the risk of mortality, myocardial infarction and heart failure (chronic heart failure) in patients with CKD.…”
Section: Methods Of Researchmentioning
confidence: 99%